Para-Aortic Nodal Radiation in the Definitive Management of Node-Positive Cervical Cancer - Sanders, Jason C.; Muller, Donald A.; Dutta, Sunil W.; Corriher, Taylor J.; Ring, Kari L.; Showalter, Timothy N.; Romano, Kara D. (Frontiers in Oncology, 2021)
Objectives: To investigate the safety and outcomes of elective para-aortic (PA) nodal irradiation utilizing modern treatment techniques for patients with node positive cervical cancer. Methods: Patients with pelvic lymph node positive cervical cancer who received radiation were included. All patients received radiation therapy (RT) to either a traditional pelvic field or an extended field to electively cover the PA nodes. Factors associated with survival were identified using a cox proportional hazards model, and toxicities between groups were compared with a chi-square test. Results: 96 patients were identified with a mean follow up of 40 months. The incidence of acute grade ≥ 2 toxicity was 31% in the elective PA nodal RT group and 15 % in the pelvic field group (Chi-square p=0.067. There was no significant difference in rates of grade ≥ 3 acute or late toxicities between the two groups (p>0.05). The KM estimated 5-year OS was not statistically different for those receiving elective PA nodal irradiation compared to a pelvic only field, 54% vs 73% respectively (log-rank p=0.11). Conclusions: Elective PA nodal RT can safely be delivered utilizing modern planning techniques without a significant increase in severe (grade ≥ 3) acute or late toxicities, at the cost of a possible small increase in non-severe (grade 2) acute toxicities. In this series there was no survival benefit observed with the receipt of elective PA nodal RT, however, this benefit may have been obscured by the higher risk features of this population. While prospective randomized trials utilizing a risk adapted approach to elective PA nodal coverage are the only way to fully evaluate the benefit of elective PA nodal coverage, these trials are unlikely to be performed and instead we must rely on interpretation of results of risk adapted approaches like those used in ongoing clinical trials and retrospective data.